Triangulation of methods in social sciences as a foundation for university research in Latin America (Mayéutica Revista Científica de Humanidades y Artes, 2023)
The university methodological praxis in Latin America shows a tendency towards collaborative and networked work. At the same time, there is also a researchculture of urgency, of immediacy in the answers, so it is important that the Latin American University assumes as a challenge the recreation of its capacity to adaptto the contextual needs. This challenge entails a transformation in the missionary functions, including its research work; more specifically, in the application ofresearch methods that in an integrated and convergent way contribute to the understanding of reality. From this referent, the article is oriented to theconception of a proposal for the triangulation of research methods, as a way for the production and validation of knowledge in social sciences. The methodologicalapproach is based on reflexive hermeneutics, by means of focus groups and in- depth interviews, which allow the conferring of meanings to the voices of theactors (experts). The results allow to approach the understanding of triangulation as a theoretical construct, based on the contributions of different disciplines(interdisciplinary perspective). It is concluded that there is a need to resize university research praxis in the field of social sciences, based on the relevance ofmethodological triangulation as a process associated with knowledge.
Keywords: higher education; research; triangulation of methods; creativity; proactivity